Correlation of Clinical Presentations with Endometrial Pathologies in Women Presenting with Abnormal Uterine Bleeding. A Prospective Descriptive Study - Basnet, Pritha; Thakur, Achala; Agrawal, Ajay; Bhandari, Sangeeta; Sitaula, Sarita; Karki, Smriti (Birat Journal of Health Sciences, 2018)
Introduction: Abnormal uterine bleeding (AUB) is one of the common presenting symptoms in women attending gynaecology outpatient department and has remained one of the most frequent indications for hysterectomy in developing countries. Endometrial sampling is used as the first diagnostic step in AUB. Objectives: To correlate the clinical presentations with endometrial pathologies in women presenting with abnormal uterine bleeding. Methodology: This was a hospital based descriptive study carried out on one hundred and nineteen women who presented with AUB and planned for endometrial biopsy. Clinical profile of the patient was recorded and the histopathology of the sampled endometrial tissue was retrieved. Correlation of abnormal uterine bleeding with histopathology report was done using appropriate statistical test. Results: The mean age of presentation of women with abnormal uterine bleeding was 46.56 yrs ± 9.525. Irregular menstrual cycle was the commonest reason seeking treatment for AUB. The commonest histopathology among women who underwent endometrial biopsy was secretory endometrium (39.5%). Other causes identified were proliferative endometrium (21.8%), mucus flakes with hemorrhage (16%), disordered proliferative endometrium (10%), pill endometrium (5%) ,endometritis (5.9%), endometrial carcinoma (1.7%),endometrial hyperplasia without atypia (1.7%). Conclusion: The nature of endometrial pathology is varied across the entire spectrum of women presenting with abnormal uterine bleeding. Knowledge of endometrial pathology helps in directing specific management and can provide better care to women presenting with abnormal uterine bleeding. BJHS 2018;3(1)5 : 354-356